2009
DOI: 10.1002/pen.21553
|View full text |Cite
|
Sign up to set email alerts
|

Melt viscoelastic properties of peroxide cured polypropylene‐ethylene octene copolymer thermoplastic vulcanizates

Abstract: The dynamic viscoelastic properties of uncrosslinked and dynamically crosslinked blends of polypropylene (PP) and ethylene octene copolymer (EOC) were investigated in the melt state to study the mechanism of reinforcement, influence of particle size, and kinetics of modulus recovery. Dynamic vulcanization was performed by coagent assisted peroxide crosslinking system. Addition of peroxide in PP/EOC blend involves two major competing reactions: crosslinking in EOC and degradation of PP by β chain‐scission. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Appearance of the plateau region in the low frequency region results from the formation of highly ordered structure or network structure. In case of TPVs, the crosslinked EOC particles form a 3D network‐structure embedded in the PP matrix by segmental interdiffusion mechanism 12. It can be postulated that the network structure, mainly aggregates/agglomerates of crosslinked rubber particles tend to collapse and deform to exhibit higher shear thinning behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appearance of the plateau region in the low frequency region results from the formation of highly ordered structure or network structure. In case of TPVs, the crosslinked EOC particles form a 3D network‐structure embedded in the PP matrix by segmental interdiffusion mechanism 12. It can be postulated that the network structure, mainly aggregates/agglomerates of crosslinked rubber particles tend to collapse and deform to exhibit higher shear thinning behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The blend was hydrolyzed and water crosslinked in a twin screw extruder. The authors' earlier work focused on the preparation of peroxide cured PP/EOC TPVs with special attention to understand the reinforcement mechanism through melt rheological characterization techniques 12. Furthermore, it was found that peroxide cured PP/EOC TPVs in presence of a co‐agent showed better melt and solid state properties when compared with peroxide‐crosslinked PP/EPDM TPVs 13…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [47,51,53] , flattening of the curve G' is due to the three-dimensional network formation. In nanocomposites, this behavior is observed in systems with intercalated and/ or exfoliated structures, and this is known as pseudosolid behavior [54] .…”
Section: Oscillatory Rheometrymentioning
confidence: 99%
“…Lai et al [16] investigated the fracture behavior and physicomechanical properties of peroxide cured PP/EOC TPVs. As a part of the extensive research work on the peroxide cured PP/EOC TPVs, our earlier report deals with the influence of different peroxides [17], different coagents [18] and different mixing sequences [19,20] on the solid and melt state viscoelastic properties of PP/EOC TPVs. The present study primarily aims to evaluate the performance of the coagent assisted peroxide cured PP/EOC TPVs as a potential alternative to the conventional PP/EPDM TPVs.…”
Section: Introductionmentioning
confidence: 99%